DEVELOPMENT OF SKILLS ADOPTED IN THE FORMATIVE ASSESSMENT PROCESS IN THE STUDENTS OF THE 9TH GRADE OF COLÉGIO BG 1115 "10 DE FEVEREIRO"- BENGUELA - Mendonça , José Furtado; Kuly , Maria Augusta Luis; Ngando, Cândida Rosário Mbanjangwa (Seven Editora, 2024)
This scientific research project has as its theme, development of skills adopted in the formative assessment process in the students of the 9th grade of the BG 1115 "10 de Fevereiro" school - Benguela. It started from the following research problem: how do teachers carry out formative assessment in the students of the 9th grade of the BG 1115 school "10 de Fevereiro"- Benguela? The general objective was to analyze how formative assessment contributes to the development of skills in 9th grade students of the BG 1115 "10 de Fevereiro" school - Benguela. The research is descriptive, with a mixed approach, qualitative and quantitative, to achieve the objectives we used methods of theoretical level such as bibliographic, analytical-synthetic and inductive-deductive research and empirical level, observation, interview, questionnaire, for data treatment, the mathematical-statistical procedure was used. The results reveal that the formative assessment process carried out by the teachers contributes in a reasonable way to the development of skills in the students of the 9th grade of the school under study. Teachers know some formative assessment techniques, but they assess students' learning with some insufficiencies, they do not comply with all assessment procedures, the student responds by reading in the notebook without arguing, which prevents the development of skills. The formative assessment technique (PMI) and the assessment tool (MAF) enable teachers to check and record the strengths and weaknesses of students during classes, helps the student to understand the content and thus results in meaningful learning and develops skills.DOI: https://doi.org/10.56238/sevened2024.037-091